A SELF-STUDY: IMPROVING PEDAGOGICAL CONTENT KNOWLEDGE OF PRONUNCIATION TEACHING - Anis Sundusiyah (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
This self-study was initiated when the writer closely worked with a Chinese student, improving the student's pronunciation peiformance, for several weeks. The tutorial program was intended mainly to help the student improve his pronunciation. At the same time, the writer benefited the program to conduct a self study improving her pronunciation teaching practice and her understanding of that practice. A participatory observation, several interviews and a reflective writing were taken as sources to collect the data. During the program. the writer noticed some aspects of her content knowledge were transformed and evolved. The improvement of the writer's pedagOgical content knowledge (PCK), as a result of the tutorial practice, were discussed in terms of five components suggested by Magnusson et all (1999): orientations of teaching, knowledge of curriculum, knowledge of student understanding, knowledge of assessment, and knowledge of instructional strategies. This study provides a useful inquiry for exploring how one's own practice can be used to improve teacher education courses and teacher education programs.